Optimization aspects of the biological nitrogen removal process in a full-scale twin sequencing batch reactor (SBR) system in series treating landfill leachate. Issue 9 (29th July 2018) - Remmas, Nikolaos; Ntougias, Spyridon; Chatzopoulou, Marianna; Melidis, Paraschos
ABSTRACT: Despite the fact that biological nitrogen removal (BNR) process has been studied in detail in laboratory- and pilot-scale sequencing batch reactor (SBR) systems treating landfill leachate, a limited number of research works have been performed in full-scale SBR plants regarding nitrification and denitrification. In the current study, a full-scale twin SBR system in series of 700 m 3 (350 m 3 each) treating medium-age landfill leachate was evaluated in terms of its carbon and nitrogen removal efficiency in the absence and presence of external carbon source, i.e., glycerol from biodiesel production. Both biodegradable organic carbon and ammonia were highly oxidized [biochemical oxygen demand (BOD5 ) and total Kjehldahl nitrogen (TKN) removal efficiencies above 90%], whereas chemical oxygen demand (COD) removal efficiency was slightly above 40%, which is within the range reported in the literature for pilot-scale SBRs. As the consequence of the high recalcitrant organic fraction of the landfill leachate, dissimilatory nitrate reduction was restricted in the absence of crude glycerol, although denitrification was improved by electron donor addition, resulting in TN removal efficiencies above 70%. Experimental data revealed that the second SBR negligibly contributed to BNR process, since carbon and ammonia oxidation completion was achieved in the first SBR. On the other hand, the low VSS/SS ratio, due to the lack of primary sedimentation, highly improved sludge settleability, resulting in sludge volume indices (SVI) below 30 mL g –1 .